Problems and Weaknesses of Thailand’s drug policy over the past decade - Lortanapaisan, Tanaroj (Thai Social Science Journal, 2025)
The study of problems and weaknesses of Thai drug policy over the past decade is a qualitative study. The objective is to find the important factors that affect the failure of Thai drug policy over the past decade. The study found that there are 4 main factors that affect the effectiveness of Thai drug policy: 1. Thai drug policy focuses more on punishment than rehabilitation from the policy of declaring war on drugs in the early stages. It has only a short-term effect on reducing the prevalence of drugs. There are human rights problems and insufficient detention. 2. Inadequate infrastructure for drug rehabilitation. There are limited treatment centers and insufficient resources. There is a lack of experts and good models, causing those who are being treated to return to using drugs when they leave treatment. 3. Law enforcement officers target communities and target individuals disproportionately. They focus on communities with economic and social vulnerabilities. Poverty, lack of education and limited employment opportunities create an environment where drug use makes the rural poor, who are often excluded from the main economic and social system. 4. Lack of prevention policies and inadequate education. Lack of comprehensive school education programs. These programs are often superficial and lack depth.